Geographic distribution of malaria in Nepal - Ghimire, Kabita (Kansas State University, 2016)
The malaria burden has decreased in Nepal between 1988 and 2013. However, there are challenges to completely eradicating the disease. Malaria patterns in a few endemic districts have not changed, and higher malaria case rates have been detected within districts which otherwise were categorized as low endemic areas. Underlying biophysical, socioeconomic, and behavioral factors influence malaria transmission and create region-specific patterns. This research employs various concepts, tools, and techniques to understand the geographic distribution of malaria in Nepal. In this research, malaria prevalence patterns were investigated at multiple spatial and temporal scales. The study identifies malaria hot spots, describes their characteristics and examines shifts in malaria hot spots between 1988 and 2013. Within that 26-year time span, 267,121 confirmed malaria cases were recorded. Thirty-nine of 75 districts were identified as malaria hot spots in Nepal. Based on the frequency, persistence and proportion of caseloads each year, the identified hotspots were grouped into five categories; stable, disappearing, emerging, reemerging, and intermittent. The research also investigated the relationship between climatic factors and malaria frequency, and found that temperature and precipitation during the monsoon and non-monsoon seasons played significant roles in determining the absence and presence of malaria and low and high frequency of malaria distribution at the district level. The dissertation also presents the findings of a study that investigated malaria–related knowledge, perceptions and practices among adults in Nepal, specifically knowledge about its signs, symptoms, consequences, and the availability and use of prevention tools. Although a significant portion of respondents had heard of malaria there was wide variation in their knowledge about specific information related to the disease. Locality, age, household size, education, and income were significantly associated with malaria–related knowledge.
Keywords: Malaria epidemiology; Climate; Malaria pattern; Malaria geography; Nepal; Malaria knowledge